Parental Stress, Depression, and Participation in Care Before and During the COVID-19 Pandemic: A Prospective Observational Study in an Italian Neonatal Intensive Care Unit - Bua, Jenny; Mariani, Ilaria; Girardelli, Martina; Tomadin, Murphy; Tripani, Antonella; Travan, Laura; Lazzerini, Marzia (Frontiers in Pediatrics, 2021)
Background: Recent studies reported, during the COVID-19 pandemic, increased mental distress among the general population and among women around the childbirth period. COVID-19 pandemic may undermine the vulnerable well-being of parents in Neonatal Intensive Care Units (NICUs) Objective: Our study aimed to explore whether parental stress, depression and participation in care in an Italian NICU changed significantly over three periods: pre-pandemic (T0), low (T1) and high COVID-19 incidence (T2). Methods: 152 parents were assessed with the Parental Stressor Scale in the NICU (PSS:NICU), Edinburgh Postnatal Depression Scale (EPDS) and Index of Parental Participation (IPP). To estimate score differences among the three study periods a non-parametric analysis was performed. Correlation among scores was assessed with Spearman rank coefficient. Results: No significant differences in the median PSS:NICU, EPDS and IPP scores were observed over the three periods, except for a slight increase in the PSS:NICU parental role sub-score in T2 (T0 3.3 [2.3-4.1] vs T2 3.9 [3.1-4.3]; p= 0.038). A significant though weak positive correlation was found among scores. Conclusions: This study suggests that parental stress and depression may be contained during the COVID-19 pandemic, while participation may be ensured.